High utilization of fossil fuel increases the level of carbon dioxide in the atmosphere and results in global warming phenomenon. These things establish the world’s thought to look for the other alternative energy that can reduce the use of fossil fuel even to be replaced by the substitute. Recently, Indonesia has been doing the research of microalgae as a feedstock of an alternative biofuel. Fatty acid content that microalgae have is also high to produce biofuel. The steps used in this research - TRI PRARTONO; MUJIZAT KAWAROE; DAHLIA WULAN SARI; DINA AUGUSTINE (Bogor Agricultural University, Indonesia, 2010)
High utilization of fossil fuel increases the level of carbon dioxide in the atmosphere and results in global warming phenomenon. These things establish the world’s thought to look for the other alternative energy that can reduce the use of fossil fuel even to be replaced by the substitute. Recently, Indonesia has been doing the research of microalgae as a feedstock of an alternative biofuel. Fatty acid content that microalgae have is also high to produce biofuel. The steps used in this research is a 7 days cultivation, harvesting, extraction using hexane, and fatty acid identification using Gas Chromatography of microalgae species. Fatty acid component in some species such as Chlorella sp., Scenedesmus sp., Nannochloropsis sp., and Isochrysis sp. is between 0.21-29.5%; 0.11-25.16%; 0.30-42.32%; 2.06-37.63%, respectively, based on dry weight calculation. The high content of fatty acid in some species of microalgae showed the potential to be the feedstock of producing biofuel in overcoming the limited utilization from petroleum (fossil fuel) presently.